Learning Strategies at SD Muhammadiyah 1 and Muhammadiyah 2 Taman during the Covid 19 Pandemic - Zulqoh Rosyada Ifat; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to describe the concepts and learning strategies at SD Muhammadiyah 1 & 2 Taman in the era of the covid19 pandemic. In the research process this time using data collection techniques by interviewing, observing, and also taking photos with resource persons during the research process. This study aims to reveal and conclude how learning can take place even though not with face-to-face meetings as they should.